Knowledge of Posology Signifies to Find out Similimum in Bronchial Asthma. (Advancements in Homeopathic Research, 2022)
Dr. Hahnemann’s concept of Posology is described in different editions of Organon of Medicine. The treatment of the dynamic illness needs the exact dynamic strength which we called posology and that is responsible for cure all the cases that are treated in out patients department of P.D. Jain Homoeopathic Medical College, Parbhani. At first visit and every follow up disease condition is noted. Diet and regimen of patient are maintained properly.
Keywords: Posology; Dose; Repetition; Water Potency